Requirements for utilization of CREB binding protein by hypersensitive site two of the β-globin locus control region - Johnson, Kirby D. (Oxford University Press, 2002)
Strong transactivation of the β-globin genes is conferred by the β-globin locus control region (LCR), which consists of four erythroid-specific DNase I hypersensitive sites (HS1–HS4). HS2 has a powerful enhancer activity dependent upon tandem binding sites for the erythroid cell- and megakaryocyte-specific transcription factor NF-E2. An important co-activator-mediating transactivation by HS2 is the histone acetyltransferase (HAT) CREB binding protein (CBP). We showed previously that recruitment of a GAL4-CBP fusion protein to HS2 largely bypassed the requirement of the NF-E2 sites for transactivation. To determine whether GAL4-CBP recruitment is sufficient for transactivation, we assessed the importance of cis-elements within HS2. Docking of GAL4-CBP upstream of an Aγ-globin promoter lacking HS2 only weakly activated the promoter, indicating that HS2 components are required for GAL4-CBP-mediated transactivation. Sequences upstream and downstream of the NF-E2 sites were required for maximal GAL4-CBP-mediated transactivation, and HAT catalytic activity of GAL4-CBP was critical. No single factor-binding site was required for GAL4-CBP-mediated transactivation. However, deletion of two sites, a CACC site and an E-box, abolished transactivation in transient and stable transfection assays. These results suggest that NF-E2 recruits CBP as a critical step in transactivation, but additional components of HS2 are required to achieve maximal enhancer activity.